KEPUASAN DAN LOYALITAS KONSUMEN KORPORAT UNTUK ACARA MICE TERHADAP KUALITAS PELAYANAN HOTEL HSTH - Prihanto, Agus (Jurnal Manajemen dan Kewirausahaan, 2013)
Tourism and Hotel businesses are moving forward, espesially for MICE event. The objectives of this research were to analyze the factors of corporate customer satisfaction and loyalty on MICE event at hotel HSTH, the difference of satisfaction and loyalty beetwen governmental and non-governmental institutions, and to form the strategies of Hotel HSTH. It was conducted by using Structural Equation Modelling (SEM), Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI) and Custommer Loyalty Index (CLI). Based on the five dimension of Parasuraman, the most important factor was tangible dimension. The recommendations were: to upgrade all atribute espesially from tangible dimension and other atribute; to increase the knowledge of the hotel staff; and to monitor program and supervisory of the working quality.